Generalised Difference Sequence Space of non-absolute Type - A.H. Ganie; S. A. Lone; A. Afroza (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
It was Shiue [16] who have introduced the Cesaro spaces of the type Cesp and Ces1.In view of Chiue, we shall introduce and study some properties of generalised Cesaro difference sequence space. We also examine some of their basic properties viz., BK property and some inclusions relations will be taken care of.